ISC2 CISSP Certified Information Systems Security Professional Official Study Guide - Chapple, Mike; Stewart, James Michael; Gibson, Darril (John Wiley & Sons, Inc., 2024)
ISC2 Certified Information Systems Security Professional (CISSP) Official Study Guide, 10th Edition has been completely updated based on the latest 2024 CISSP Detailed Content Outline. This bestselling Sybex Study Guide covers 100% of the CISSP objectives. You'll prepare smarter and faster with Sybex thanks to expert content, knowledge from our real-world experience, access to the Sybex online interactive learning environment, and much more. Reinforce what you've learned with key topic Study Essentials and chapter review questions